Prolonged Pediatric Extracorporeal Membrane Oxygenation Support with Cardiopulmonary Failure in Juvenile Myelomonocytic Leukemia. (13th January 2020) - Bartkevics, Maris; Hennig, Bert; Gungor, Tayfun; Ammann, Roland; Kadner, Alexander
Abstract : We report a case of a child survival after extracorporeal membrane oxygenation (ECMO) support of 25 days for cardiopulmonary failure and septic shock in the context of juvenile myelomonocytic leukemia (JMML). ECMO support is still a matter of debate for the management of septic patients with malignancy. However, these patients are at increased risk for early death secondary to pulmonary complications due to leukostasis, direct pulmonary infiltration with WBC, and systemic inflammatory response syndrome following malignant cell lysis. Despite the high risk of complications, ECMO support must be discussed as part of management, providing better outcome in this group of patients.